Immune responses to biosurfaces : Mechanisms and therapeutic interventions - Lambris, John D.; Ekdahl, Kristina N.; Ricklin, Daniel; Nilsson, Bo (Advances in Experimental Medicine and Biology, 2015)
The collection of chapters in this proceedings volume brings together research from academic and industry scientists and clinical development experts who are focused on contemporary and emerging aspects of improving treatments employing biosurfaces. Interactions between biomaterial implants, devices, cell therapies, and whole organ transplants frequently trigger activation of body defense systems and responses that negatively affect the clinical outcome. Optimal tissue integration and modulation of foreign body reactions is therefore essential for preserving anticipated functions and avoiding adverse effects. Topics covered include mechanistic and applied research within the fields of extracorporeal devices, soft and hard tissue implants, tissue and biomaterial-targeting, therapeutic modulation of foreign body reactions, cell encapsulations, as well as cell and whole organ transplantation.